Pengembangan Model Pembelajaran Berbasis Proyek (Project Based Learning) Untuk Meningkatkan Sikap Peduli Lingkungan Pada Anak Usia Dini - Uum Suminar; Yus Alvar Saabighoot; Esya Anesty Mashudi; Maman Rumanta; Ika Rizqi Meilya (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to conduct a limited trial of a hypothetical project-based learning (PjBL) model to increase environmental awareness in early childhood. This research uses Research and Developmentnet. The research subjects were teachers and early childhood students from kindergartens in Serang City who were determined through a multistage cluster sampling technique. The data in this study were collected through questionnaires, observations, interviews, FGDs and documentation/literature studies. Research data analysis was carried out through data analysis on the development of a hypothetical model and testing the effectiveness of the model. The results of limited trials of project-based learning models to improve environmental care attitudes in early childhood were declared feasible and effective. The feasibility of the learning model was assessed by material experts to get the "Good" category. The feasibility of supporting media in the form of module books/guidelines was assessed by media experts as included in the "Very Good" category. The feasibility of the instrument was assessed by instrument experts into the "Very Good" category. The project-based learning model developed in this study was declared effective for increasing early childhood environmental care attitudes. The average results of the assessment of environmental care for early childhood showed an increase after being given 5 treatments. The results of hypothesis testing show that there is a significant difference in the average rating of caring for the environment in early childhood using a project-based learning model